Influence of Electrode Spacing on Grounding Resistances in Electrical Networks for Effective Lightning Protection - Anedi Oko Ganongo; Rodolphe Gomba; Nianga-Apila; Linné Lovel Atsembou Obita; Branham Jacques Lévi Makanga; Mathurin Gogom; Gilbert Ganga (Advances in Technology Innovation, 2026)
This study aims to analyze the influence of inter-electrode spacing on grounding resistance in high-voltage transmission networks. A simplified analytical model is applied to a case study on the Djiri-Ngo 220 kV line (Republic of the Congo), considering two representative soil types: clayey and siliceous sand. The grounding resistance is calculated by varying the number of electrodes and their spacing. The results show that increasing electrode spacing reduces grounding resistance. In certain configurations, the improvement exceeding 50 % when the spacing is increased from 5 m to 25 m. A saturation threshold is identified, beyond which further increases in spacing yields diminishing returns. Electrode spacing proves to be a key design factor, sometimes more influential than the number of electrodes. The proposed parametric geometric analysis offers a practical and cost-effective strategy for grounding system design, emphasizing the importance of adapting configurations to local geotechnical conditions.